2017
DOI: 10.1108/jes-04-2015-0065
|View full text |Cite
|
Sign up to set email alerts
|

Income convergence in India: evidence from nonparametric panel data

Abstract: Purpose The purpose of this paper is to investigate convergence hypothesis in a balanced panel of 22 Indian states for the time period of 1980-81 to 2010-11 by applying nonparametric model setting in a panel framework. Design/methodology/approach The present study uses nonparametric and semi-parametric panel data methods to test the absolute and conditional convergence, respectively, and examines the income convergence using nonparametric panel data methods with state specific effects taken into consideratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…This study attempts to address some of the above noted issues in the convergence literature focusing on the Indian case. Taking states as the unit of measurement, some studies identified a divergence in India's overall economic growth but others found a convergence (Ghosh et al., 2013; Nagaraj et al., 2000; Sachs et al., 2002; Sofi & S., 2017). Recent developments that probe such tendency at a district level also provide contrasting results (Chanda & Kabiraj, 2020; Das et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…This study attempts to address some of the above noted issues in the convergence literature focusing on the Indian case. Taking states as the unit of measurement, some studies identified a divergence in India's overall economic growth but others found a convergence (Ghosh et al., 2013; Nagaraj et al., 2000; Sachs et al., 2002; Sofi & S., 2017). Recent developments that probe such tendency at a district level also provide contrasting results (Chanda & Kabiraj, 2020; Das et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the literature on the convergence hypothesis of Barro and Sala-i-Martin (1992) explains the differences in levels and growth rates of income across different economies or regions in an economy (to cite a few among others, Purfield 2006;Rao et al 1999;Sachs et al 2002;Trivedi 2003). A few studies have found evidence of absolute divergence with conditional convergence (see among others, Chakraborty and Chakraborty 2018;Cherodian and Thirlwall 2015;and Sofi and Durai 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Regional patterns of growth, however, have been asymmetrical, leading to an accentuation in interregional disparities in economic development (Nagaraj et el. 2000;Sachs et al 2002;Bhattacharya and Sakthivel 2004;Purfield 2006; Sodwriwiboon and Kalra 2010; Agarwalla and Pangotra 2011; Sofi and Raja Sethu Durai 2017;OECD 2017). Reducing regional disparities is, therefore, a major policy concern, as the regions left behind in economic development could be more prone to social tensions and fissiparous tendencies (Shankar and Shah 2003;Sodwriwiboon and Kalra 2010).…”
mentioning
confidence: 99%